Whichever intelligence makes you happy: The role of academic, emotional, and practical abilities in predicting psychological well-being. (1st October 2018) - Altaras Dimitrijević, Ana; Jolić Marjanović, Zorana; Dimitrijević, Aleksandar
Abstract: Recent findings suggest a positive effect of intelligence on psychological well-being but remain inconclusive as to whether this criterion would be better predicted by drawing on emotional and practical abilities–besides traditional "academic" ones–and whether any path from intelligence to well-being bypasses socioeconomic status. We investigated these issues with a sample of 288 working adults ( N in path analyses = 157), employing three standard tests of academic intelligence (Matrix Reasoning, Verbal Analogies, General Knowledge); the Mayer-Salovey-Caruso Emotional Intelligence Test; the practical sections of Sternberg's Triarchic Abilities Test to assess practical intelligence; and Ryff's Scales of Psychological Well-Being. Hierarchical regression analyses yielded academic intelligence (Step 1), specifically Matrix Reasoning, and emotional intelligence (Step 2, with practical intelligence), specifically Understanding and Managing Emotions, as independent predictors of well-being. Subsequent path analyses revealed that the effect of academic intelligence on well-being was indirect (mediated by socioeconomic status) and the effect of emotional intelligence a direct one, the latter also being stronger and primarily due to the Managing Emotions branch. While expanding the evidence on the real-life utility of academic intelligence, the present results draw special attention to knowing/reasoning about emotions as an incremental predictor of well-being, the implications of which are discussed. Highlights: Emotional intelligence predicted well-being over traditional academic abilities. The effect of academic intelligence was mediated by socioeconomic status (SES). Emotional intelligence had a direct effect on well-being, unrelated to SES or age. Managing Emotions was the strongest component-level predictor of well-being.